The Continuum of Sexual Violence - Kelly, Liz (Women, Violence and Social Control, 1987)
This chapter discusses the application of the concept of the continuum of sexual violence to research on, and discussion of, the issue of sexual violence. Two of the original aims of the research were to explore the links between the different forms of sexual violence and to investigate the idea, which arose whilst working in a refuge for battered women, that most women have experience of sexual violence in their lifetime.1 Whilst analysing the in-depth interviews carried out with women, I begin to use the concept of a continuum of sexual violence to describe the findings in the two areas.